2023
DOI: 10.1093/jnci/djad070
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function in patients with ovarian cancer treated with poly (ADP-ribose) polymerase (PARP) inhibitors

Abstract: Background Poly (ADP-ribose) polymerase inhibitors (PARPi) have revolutionized the treatment of ovarian cancer; however, real-world data on kidney function among patients treated with PARPi are lacking. Methods We identified adults treated with olaparib or niraparib between 2015-2021 at a major cancer center in Boston, Massachusetts. We determined the incidence of any acute kidney injury (AKI), defined as a ≥ 1.5-fold rise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Gupt et al. compared the renal function of olaparib and niraparib, and reported that although both showed decreased renal function, there was no difference between the two drugs ( 8 ). We investigated the correlation in kidney function between maintenance treatment and chemotherapy given before maintenance treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gupt et al. compared the renal function of olaparib and niraparib, and reported that although both showed decreased renal function, there was no difference between the two drugs ( 8 ). We investigated the correlation in kidney function between maintenance treatment and chemotherapy given before maintenance treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Renal function deterioration due to the use of PARP inhibitors has become a topic of discussion ( 8 ). In this study, we investigated hematological toxicity and renal function following chemotherapy and maintenance therapy among the three groups including bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…PARPis may cause pseudo-AKI, but this largely resolves with drug discontinuation. 9 Measured GFR or eGFR via cystatin C does not show significant change from baseline eGFR before treatment. Despite these observations, the data on the long-term safety of PARPis are limited.…”
Section: Poly(adp-ribose) Polymerase Inhibitorsmentioning
confidence: 94%
“…Targeted molecular anticancer agents, pseudo-AKI, and true kidney adverse effects[6][7][8][9][10] AIN, acute interstitial nephritis; ATI, acute tubular injury; ALK, anaplastic lymphoma kinase; BCR-ABL, breakpoint cluster region-abelson; BRAF, v-raf murine sarcoma viral oncogene homolog B1; CDK, cyclin-dependent kinase; MATE, multidrug and toxin extruder; MET, mesenchymal-epithelial transition; ND, not determined; OCT, organic cation transporter; PARP, poly(ADP-ribose) polymerase.GFR in Cancer Part 2, Kitchlu et al CJASN 19: 1073-1077, August, 2024 1075…”
mentioning
confidence: 99%
“…Other chemopreventive agents that may affect renal function in ovarian cancer include targeted therapies such as bevacizumab and PARP [Poly (ADPribose) polymerase] inhibitors. Bevacizumab can cause proteinuria and hypertension, which can lead to renal impairment, while PARP inhibitors may increase the risk of acute kidney injury (AKI) (23,24).…”
Section: Renal Histopathology Following Ovarian Cancermentioning
confidence: 99%